if
![\cos( \beta + \sin( \beta ) ) = \sqrt{2} \cos( \beta ) \cos( \beta + \sin( \beta ) ) = \sqrt{2} \cos( \beta )](https://tex.z-dn.net/?f=+%5Ccos%28+%5Cbeta++%2B++%5Csin%28+%5Cbeta++%29+%29++%3D++++%5Csqrt%7B2%7D++%5Ccos%28+%5Cbeta+%29+)
then show that
![\cos( \beta) - \sin( \beta ) = \sqrt{2} \sin( \beta ) \cos( \beta) - \sin( \beta ) = \sqrt{2} \sin( \beta )](https://tex.z-dn.net/?f=+%5Ccos%28+%5Cbeta%29++-++%5Csin%28+%5Cbeta+%29++%3D++%5Csqrt%7B2%7D++%5Csin%28+%5Cbeta+%29+)
Answers
Answered by
18
Que :-
Given that :- CosA + SinA = √2 CosA
Then Prove That:- Cos A - SinA = √2 SinA.
Solution :-
CosA + SinA = √2 CosA
Squaring on both the sides. we get,
( CosA + SinA )² = ( √2 cosA)²
=> Cos²A + Sin²A + 2SinA. CosA = 2 Cos²A
=> Sin²A + 2SinA. CosA = 2 Cos²A - Cos²A
=> Sin²A + 2SinA. CosA = Cos²A
Adding Sin²A both the sides. we get,
=> Sin²A + Sin²A + 2SinA. CosA = Cos²A + Sin²A
=> 2 Sin²A = Sin²A + Cos²A - 2SinA. CosA
=> 2 Sin²A = (CosA - SinA)²
=> CosA - SinA = √(2 Sin²A)
=> CosA - SinA = √2 SinA.
Hence Proved.
Given that :- CosA + SinA = √2 CosA
Then Prove That:- Cos A - SinA = √2 SinA.
Solution :-
CosA + SinA = √2 CosA
Squaring on both the sides. we get,
( CosA + SinA )² = ( √2 cosA)²
=> Cos²A + Sin²A + 2SinA. CosA = 2 Cos²A
=> Sin²A + 2SinA. CosA = 2 Cos²A - Cos²A
=> Sin²A + 2SinA. CosA = Cos²A
Adding Sin²A both the sides. we get,
=> Sin²A + Sin²A + 2SinA. CosA = Cos²A + Sin²A
=> 2 Sin²A = Sin²A + Cos²A - 2SinA. CosA
=> 2 Sin²A = (CosA - SinA)²
=> CosA - SinA = √(2 Sin²A)
=> CosA - SinA = √2 SinA.
Hence Proved.
Anonymous:
Amazing...✔️✔️
Similar questions
Geography,
8 months ago